Exploration of the causes of cerebrospinal fluid leakage after endoscopic endonasal surgery for sellar and suprasellar lesions and analysis of risk factors - Xiong, Yicheng; Liu, Yajing; Xin, Guo; Xie, Shenhao; Luo, Hai; Xiao, Liming; Wu, Xiao; Hong, Tao; Tang, Bin (Frontiers in Surgery, 2022)
Objective Postoperative cerebrospinal fluid (CSF) leakage following endoscopic endonasal surgery (EES) is a frequent complication. This study aims to identify potential risk factors of postoperative CSF leakage. Methods A retrospective review of 360 patients who underwent EES was included. The associations between postoperative CSF leakage and patient demographics, medical history, tumor characteristics, and intraoperative repair techniques were analyzed; the diagnosis and repair of postoperative CSF leakage were also introduced. Results Postoperative CSF leakage occurred in 14 patients (3.9%), 2 of them cured by lumbar cistern drainage, 12 underwent endoscopic repair. Among these 12 cases, 3 were repaired twice, and the rest were cured the first time. During the repair surgery, insufficient embedded fat was detected in one case detected, seven with breached inner artificial dura, three had vascularized pedicle nasoseptal flap (VP-NSF) displacement, two with VP-NSF perforation, two with VP-NSF inactivation, and one with imperfect adherence to VP-NSF to the skull base. Eight cases had intracranial infections. Excluding one case who died of severe intracranial infection, the rest were cured and discharged without obvious sequelae. Multivariate analysis revealed that the suprasellar lesion, subarachnoid invasion, and intraoperative grade 3 flow CSF leakage were the risk factors of CSF leakage after operation, while the bone flap was a protective factor. Conclusion Bone flap combined with VP-NSF and iodoform gauze for skull base reconstruction is recommended in high-risk patients, while postoperative lumbar cistern drain remains dispensable.